1988
DOI: 10.1007/bf00320634
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of pluripotent hemopoietic progenitor cells in myelodysplastic syndromes

Abstract: Pluripotent (CFU-MIX), erythroid (BFU-E) and granulocyte/macrophage (CFU-GM) progenitor cells were examined in bone marrow (BM) from 23 patients with myelodysplastic syndromes (MDS). Patients were grouped according to the FAB classification: Refractory anemia (RA), n = 3; RA with ring sideroblasts (RARS), n = 3; RA with excess of blasts (RAEB), n = 8; RA with excess of blasts in transformation (RAEBt), n = 7; chronic myelomonocytic leukemia (CMML), n = 2. In FAB groups RA, RARS, RAEB and RAEBt CFU-GM concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 17 publications
1
13
0
1
Order By: Relevance
“…The findings of this report are in accordance with the in vitro short-term culture data in MDS marrow, where a very low plating efficiency is the rule 29 and could signify a defective maintenance of hematopoietic progenitors in MDS marrow, which is contributing to the marrow failure. We have also found that by adding a combination of hematopoietic growth factors, a significant increase in the plating efficiency of MDS marrow and blood progenitors can be achieved, presumably by an anti-apoptotic mechanism (manuscript in preparation).…”
Section: Tunel Technique In Separated Cd34supporting
confidence: 80%
“…The findings of this report are in accordance with the in vitro short-term culture data in MDS marrow, where a very low plating efficiency is the rule 29 and could signify a defective maintenance of hematopoietic progenitors in MDS marrow, which is contributing to the marrow failure. We have also found that by adding a combination of hematopoietic growth factors, a significant increase in the plating efficiency of MDS marrow and blood progenitors can be achieved, presumably by an anti-apoptotic mechanism (manuscript in preparation).…”
Section: Tunel Technique In Separated Cd34supporting
confidence: 80%
“…Although not routinely available at all centers, these progenitor cell assays can provide a sensitive screening parameter for undiagnosed cytopenias (Tennant, Jacobs et al 1986; Valent 2012). In MDS specifically, they may also have prognostic significance in that low growth suggests a poorer prognosis (Geissler, Hinterberger et al 1988; Shih, Chiu et al 1991). Since 2007 we have been performing these BFUE assays in diagnostically challenging (often 2 nd opinion) cases with the hopes of gaining additional insight into better diagnosis of bone marrow failure states.…”
mentioning
confidence: 99%
“…A decreased number of CFUs is confirmatory (but not specific) for the diagnosis MDS [15][16][17]. On the other hand, however, a normal CFU count does not role out the diagnosis of MDS.…”
Section: Pathogenesis Classification and Treatment Of Myelodysplastmentioning
confidence: 86%